REFLEXIONES A PARTIR DEL TERREMOTO DE FEBRERO DE 2010 EN CHILE - Aigneren, Miguel (La Sociología en sus Escenarios, 2010)
Abstract. The Chilean’s political elite has worried to say one and thousand times that "the institutions work and have responded before the earthquake", but nobody indicates the quality nor the competitions of those institutions. Without doubts, the recent earthquake that shook the country showed the fact that in Chile although organisms exist public were not able nor to prepare opportune answers to the catastrophe, nor to respond of effective way after to take place one like which we finished being present at 27 of February to the 03:34 am an earthquake of measured degree 8.8 in the scale of Richter took place, in the South center of the country. At the same time a series of errors and irresponsibility’s on the part of the organisms that demonstrated that the country still is a cat with desire of being jaguar. Only six minutes later the epicenter was known (to about 90 kilometers to the northwest of the city of Conception, that is to say in the Pacific Ocean), nevertheless the Hydrographic and Oceanographic Service of the Navy of Chile (SHOA), organism that had to position the technical instruments to evaluate if there is or not a tidal wave, not only did not work, but also that did not give warning nor followed the protocol existing. The other organism of State, denominates ONEMI, the National Office of Emergencies, at any moment indicated that there was no tidal wave. Today, by voices of the survivors, we know that to the 3:52 the first wave takes place, of a total of three. The last wave takes place to the 06:32 hrs. Around one hour later the undersecretary of the Interior discarded the possibility of tsunami. Resumen. El epilogo que deja el terremoto del 27 de febrero de 2010 es el de un estado inoperante, errático e ineficiente. Por ejemplo, el terremoto dejó al descubierto el rostro de una educación para una vida totalmente mercantilizada. La sociedad chilena está fracturada, no respondió como en ocasiones anteriores y más dramáticas con solidaridad social sino con pillaje, no de "lumpen o delincuentes" barriales" como se quiso decir sino que las mismas clases medias se dedicaron al saqueo y pillaje, no de productos de la canasta familiar sino a robar electrodomésticos y artículos suntuarios de las grandes tiendas y supermercados